Role of Fertilizers in Buiding-Up the Fertility of Eroded soils - Prasad, R.; bhan, Suraj (Journal of Soil and Water Conservation, 2022)
Modern agriculture is largely dependant upon the maintenance of a favourable eqilibrium between losses and gains of available plant nutrient elements in soils. Erosion, cropping, leaching and volatization are the principal pathways whereby nutrient elements are removed from soils. The crops remove only those elements taken up by them during period of their growth, but leaching losses in humid.. regions tend to be governed by the degree of mobility of nutrient elements in soils. Volatization losses are generally thought to be limited to nitrogen and sulphur, but the quantitative data relating to the extent of such losses are very meagre.